CCTA-Guided Selective Invasive Coronary Catheterization: A Strategy to Reduce Contrast Volume and Improve Efficiency - Jorge Dahdal; Ruurt Jukema; Aernout G. Somsen; Eline Kooijman; Ellaha Wahedi; Jorrit S. Lemkes; Pieter G. Raijmakers; Ton Heestermans; Niels van Royen; Paul Knaapen; Ibrahim Danad (Diagnostics)
Background: Symptomatic patients with unilateral obstructive coronary artery disease (CAD) identified by coronary computed tomography angiography (CCTA), involving either the right or left coronary artery, typically undergo per-protocol bilateral coronary visualization during invasive coronary angiography (ICA). However, a selective visualization approach may be sufficient. Objectives: The objectives of this study were to assess the accuracy of CCTA in excluding hemodynamically significant coronary stenosis in patients with unilateral CAD and to evaluate whether a CCTA-guided selective ICA strategy can reduce procedure time and contrast agent use. Methods: In this cross-sectional cohort study, 454 patients with clinically suspected stable CAD who underwent CCTA prior to ICA were included. The study population consisted of 190 patients with unilateral obstructive CAD, defined as ≥50% diameter stenosis on CCTA, and an absence of obstructive CAD on the contralateral side. ICA with invasive functional assessment was used as the reference standard. Results: CCTA demonstrated a high accuracy, 97.4% (95% CI: 94–99%), in excluding hemodynamically significant disease in the contralateral arteries without obstructive CAD. Compared to the conventional ICA approach, a CCTA-guided selective visualization strategy resulted in significant reductions in procedure time and contrast agent usage: procedure time and contrast agent usage were reduced by 27% (95% CI: 12.1–47.5%) and 46.8% (95% CI: 27.5–67.0%), respectively. Conclusions: In patients with unilateral obstructive CAD identified by CCTA, a CCTA-guided selective ICA visualization strategy is highly accurate in ruling out hemodynamically significant CAD on the contralateral side. Additionally, this unilateral ICA approach has the potential to reduce both contrast agent usage and procedure time compared to the conventional bilateral visualization strategy.